PENGARUH SUPLEMENTASI TEPUNG KULIT MANGGIS (Garcinia mangostana L.) TERHADAP PERFORMAN, PRODUKSI KARKAS, PERLEMAKAN, PROFIL KOLESTEROL, DAN KUALITAS KIMIA DAGING AYAM BROILER - , Siska Fitria ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The experiment was conducted to identify the effect of pericarp mangosteen (Garcinia mangostana L.) supplementation as feed additives on performance, carcass production, fatness, cholesterol, and chemical quality of broiler meat. Ninety broiler males of Lohmann strain of 7 days of age were distributed in 5 treatments with 3 replications of 6 broiler chickens each. The broilers were kept until 35 days of ages. Data collected were those of performance, carcass production, chemichal quality of meat, peroxide value, cholesterol profile, and fatty acid profil of meat. The data were analized using one way ANOVA of a complede randomized design (CRD) and then were tested using Duncanâs new Multiple Range Test (DMRT). The result showed that feed treatments of 0.00 (control), 0.50, 1.00, 1.50, and 2.00% in diets had significantly differences (P<0.01) on peroxide value (9.85